Magma emplacement: an important trigger leading to slope failures in deep‐water areas of northern continental margin of South China Sea. (7th July 2016) - Ma, Y.; Li, S. Z.; Lin, J. Q.; Liang, Q. Y.; Shi, Y. H.; Kong, L.
Abstract: Submarine slope failures are considered as a serious geo‐hazard because they can rupture undersea pipelines, and seafloor engineering facilities can be subverted by destroying the seabed stability. Submarine slope failures are widely developed in deep‐water areas of the northern continental margin of the South China Sea, yet the mechanisms involved in their generation remain poorly known. Observations have proposed that slope instability can be due either to decomposition of gas hydrate or to magma emplacement. Here, we present new high‐resolution 2D seismic data from the deep‐water areas of the northern continental margin of the South China Sea to reveal an extensive and intimate relationship between magma emplacement and slope failures. This paper shows four landslides on the Dongsha, Shenhu, Xisha and Qiongdongnan slopes that occurred at different locations of the northern continental slope of the South China Sea. There are seismic evidences that magmatic rocks commonly developed and migrated upwards to the overlying layers and they caused these layers to uplift as a dome and possibly decreased their strength and predisposition to failure. The data reveal in detail how magma emplacement influenced slope stability and the seismic reflection features of this type of submarine landslides. The findings illustrate the importance of magma emplacement resulting in slope instability. This paper proposes that magma emplacement is a basic and critical trigger leading to slope failures in the deep‐water areas of the northern continental margin of the South China Sea and establishes genetic models for this important trigger. Copyright © 2016 John Wiley & Sons, Ltd.